Traumatic Pulmonary Pseudocyst Mimicking a Congenital Cystic Lung Disease - Amjad Kanj; Hussam Tabaja; Ayman O. Soubani; Nadim Kanj (Case Reports in Pulmonology)
Traumatic pulmonary pseudocyst (TPP) is a rare entity that occurs following a trauma to the chest. It usually presents as multiple cystic lesions on thoracic imaging. It is treated conservatively and tends to completely resolve after few months. In the absence of striking signs of trauma such as rib fractures, TPP can be mistaken for other cystic lung diseases. We present a case of TPP in a 17-year-old male who was seen for mild hemoptysis after falling off a cliff. The extent of his right lower lobe cystic lesions along with the lack of major signs of trauma led to an incorrect diagnosis of congenital pulmonary airway malformation. The patient was considered for lobectomy, which he refused. Imaging of the chest repeated one and three years later showed complete resolution of the lesions.